Bullying as a social phenomenon in the youth environment - S. A. Grishaeva; S. V. Chuev; N. N. Pushkareva (Вестник университета, 2024)
The article examines the problems of  such a   social phenomenon as  bullying among youth. The issue of   relationships in a   group, especially during the period of   maturing and active development of  personality, is  very relevant. These relationships are not always constructive and aimed at   cooperation: there are often situations of   aggression that accompany the communication process in  the group. One type of   such aggressive behaviour is  bullying, the manifestations of   which are studied in   this work. The authors have conducted a   research using a  quantitative method (questionnaire survey in  82 constituent entities of   the Russian Federation) and qualitative methods (focus groups and project sessions). The most common forms of   bullying have been identified. The authors have determined the subjects that, according to   the respondents, should provide assistance to   victims of  bullying and the provocateurs of   bullying (among whom are not only aggressors, but also victims). At   the same time, as   the research results show, new questions have arisen regarding the issue of   the phenomenon, both terminological (what does modern youth understand by  bullying) and socio-psychological (what are the similarities and differences between the aggressor, provocateur, victim), which will be   solved at   the next research stages.